LB-15. A Trans-Governmental Collaborative Effort to Independently Evaluate SARS-CoV-2 Serology Assays Using Well-Characterized Sample Panels. (31st December 2020) - Shawar, Ribhi; O'Leary, Brendan; Kemp, Troy; Cherry, James; Owen, S Michele; Gallagher, Pamela; Thornburg, Natalie; Kondratovich, Marina; Satheshkumar Panayampalli, Subbian; Schuh, Amy; Lester, Sandra; Cassetti, Cristina; et al.
Abstract: Background: The emergence of the novel coronavirus, SARS-CoV-2, created a crucial need for accurate tests for diagnosis, assessment of prior infection, and understanding its natural history. Serology assays play an important role in the assessment of anti-viral immune responses and previous infections. Evaluation of serology assays with well-characterized serum and/or plasma samples is critical to determine assay performance. CDC, FDA and NCI's Frederick National Laboratory for Cancer Research (NCI-FNLCR) have established a collaborative network to independently evaluate commercial antibody tests prior to their authorization. Methods: Positive (n=30) serum samples with a range of anti-SARS-CoV-2 antibody titers (Table) and negative (n=80) serum and/or plasma samples were selected to establish performance evaluation panels (PEVs). Three PEVs with similar overall antibody titer distribution have been created. Negative samples were collected prior to 2020, before the SARS-CoV-2 pandemic. Positive samples were from patients previously confirmed to have SARS-CoV-2 using a nucleic acid amplification test. Each sample was characterized at CDC and NCI-FNLCR for presence/absence of SARS-CoV-2 IgM and IgG antibodies using a SARS-CoV-2 spike enzyme linked immunosorbent assay (ELISA). NCI-FNLCR also performed a SARS-CoV-2 spike Receptor Binding Domain (RBD) IgG ELISA. Positive samples were assessed at multiple dilutions. Manufacturers submitted their serology assays for evaluation by this program. The sensitivity of each test was assessed for each antibody class (IgG and IgM) and in a combined manner, where a positive result for either antibody was considered as a positive result. For combined specificity, a negative result meant a sample was negative for both antibodies (IgG and IgM). Number of positive samples with anti-SARS-CoV-2 spike antibodies for each panel (n=30) Results: To date, 53 serology assays have been evaluated. Sensitivity ranged from 30.0% to 100% for IgG, from 10.0% to 100% for IgM, and the combined specificity ranged from 57.5% to 100%. For 2 assays that measure total Ig, sensitivity was 96.7% and 100%. Conclusion: This program completed over 50 performance evaluations with well-characterized PEVs. Results have been used to inform FDA regulatory decisions and are publicly available on FDA's website. Disclosures: Cristina Cassetti, PhD, Nothing to disclose